(untitled) (Web of Teachers: Inderscience Research, 2025)
This paper explores the growing impact of digital accounting on modern business environments. As organizations shift from traditional bookkeeping to cloud-based and automated systems, efficiency, transparency, and accuracy in financial management have significantly improved. Using data from Deloitte, SAP, and Xero, the study highlights the advantages and challenges of digital accounting adoption in both global and Uzbek contexts. It also examines how digital tools contribute to strategic decision-making and reduce operational risks. The findings indicate that although digital accounting enhances productivity and simplifies auditing, successful implementation requires investment in human capital and cybersecurity infrastructure.